2008
DOI: 10.1007/s11814-008-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic field on calcium carbonate precipitation: Ionic and particle mechanisms

Abstract: There are two most widely reported mechanisms to study the effect of magnetic fields on calcium carbonate (CaCO 3 ) precipitate, namely ionic and particle mechanisms. The effects are most debatable because they are contrary to each other. This study explored the effects of both mechanisms in CaCO 3 deposit and total CaCO 3 precipitation using ionic and particle methods. The ionic method showed reductions in CaCO 3 deposit and total precipitation rate of CaCO 3 , whereas the particle method showed the opposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In particular, the published data concerning the regarding the effect of water magnetic conditioners on water hardness is relatively few, rather confusing due to the often-contradictory results. Some researchers confirmed that the magnetic field affected water quality and reduced water hardness [11][12][13][14][15]. While others reported that the magnetic field has no effect on the hardness of water [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the published data concerning the regarding the effect of water magnetic conditioners on water hardness is relatively few, rather confusing due to the often-contradictory results. Some researchers confirmed that the magnetic field affected water quality and reduced water hardness [11][12][13][14][15]. While others reported that the magnetic field has no effect on the hardness of water [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic treatment enhanced the growth of calcite, vaterite and aragonite crystals. Banejad and Abdosalehi [12] measured hardness of water after subjection to a magnetic field (0.05, 0.075 and 0.1 Tesla) with different flow rate (4 and 30 L/h). It was concluded that the magnetic field affected the water quality and that production of magnetic water reduces water hardness until 51 %.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms, however, are not fully understood, and controversial results had been reported in the literatures [34][35][36]. Tai et al observed the lower growth rate of calcite in the presence of magnetic field under low pH and supersaturation conditions while the growth rate seemed to increase at high pH condition [34].…”
Section: Discussionmentioning
confidence: 99%
“…Tai et al observed the lower growth rate of calcite in the presence of magnetic field under low pH and supersaturation conditions while the growth rate seemed to increase at high pH condition [34]. Saksono et al conducted the magnetic treatment during the calcium carbonate precipitation process and found the number of calcite crystals increased but with decreased crystal size [35]. Earlier, the study by Evangelos Dalas et al [36] showed that the growth rate of calcite decreased only under a relatively strong magnetic field (> 5 T).…”
Section: Discussionmentioning
confidence: 99%
“…In many research, CaCO 3 precipitation was obtained by reaction of the Na 2 CO 3 and CaCl 2 solution. Two mechanisms have been developed to address magnetic field effects on calcium carbonate precipitation, viz., (1) a direct effect on dissolved ions and (2) a magnetic effect on particles [2]. They called the first mechanism as "ionic mechanism".…”
Section: Introductionmentioning
confidence: 99%